When fitness becomes an obsession: a cross-sectional study investigating the risk of exercise addiction among athletes - Arsalan Tariq; Abdul Saad (BMJ Open Sport & Exercise Medicine)
Objective This study examines the relationship between the risk of exercise addiction and psychological factors like anxiety, depression, self-esteem and sleep quality in athletes.Methods This cross-sectional study was conducted in Lahore between August and November 2023, involving 282 athletes from five gyms engaged in bodybuilding, powerlifting or strength training. The study explored the relationship between exercise addiction risk and psychological factors, including anxiety, depression, body image distress, self-esteem, stress, obsessive-compulsive symptoms and sleep quality. Participants met specific inclusion criteria related to training frequency, duration and mental health status. Standardised questionnaires, including the Exercise Addiction Inventory, Hospital Anxiety and Depression Scale, Body Shape Questionnaire, Rosenberg Self-Esteem Scale, Obsessive-Compulsive Inventory-Revised, Pittsburgh Sleep Quality Index and Perceived Stress Scale, were used for data collection. Data were analysed using SPSS (V.24) with descriptive statistics, t-tests, analysis of variance (ANOVA), Pearson correlations and hierarchical multiple regression.Results 267 completed the study. The majority were male (85.4%), with bodybuilding (50.2%) being the most common type of training. Participants reported high levels of psychological distress, including anxiety, body image concerns and stress. Exercise addiction risk was significantly associated with body image distress (r=0.45), anxiety (r=0.42) and stress (r=0.40), while self-esteem showed a negative correlation (r= –0.36). Hierarchical regression showed psychological factors accounted for 51% of the variance in addiction risk, with body image distress and anxiety being the strongest predictors. Bodybuilders and males reported significantly higher addiction risk scores compared with other groups.Conclusion Body image dissatisfaction, anxiety and stress are significant risk factors for exercise addiction, often reflecting emotional coping over performance goals.